PENGARUH GAYA KEPEMIMPINAN, KOMUNIKASI INTERN, MOTIVASI DAN KOMPETENSI TERHADAP KINERJA KARYAWAN PT. PAGILARAN KAB. BATANG - Danar Frans Hadika, 0935020710 (Students Journal of Economic and Management, 2014)
This study is a study that examines the effect of leadership style, internal communication, motivation, and competence on employee performance. In this study, researchers used purposive sampling and obtain a sample size of 77 employees out of a total population sample of 333 employees of the company, then the results of these studies tested the data with validity and reliability, the result, the whole construct produce valid and reliable value. Further analysis researchers used multiple regression analysis to explain the relationship between these variables. The result is the motivation and competence and a significant positive effect on performance. While the styles of leadership and internal communication have no effect on performance. It can be concluded that if the level of employee motivation and high competence will produce peak performance. This is consistent with results of studies of existing theories and the results of an analysis of previous studies. It is expected that the whole range of leaders of PT. Pagilaran District of Blado to make relevant rules or policies that could improve the motivation and competence of employees, so that organizational goals can be achieved together Keywords :Leadership Style, InternalCommunication, Motivation, Competence, EmployeePerformance